Nurses’ Experiences of Providing Pain Management to Pediatric Patients in Indonesia - Lee Tzu-Ying; Nunik Nurhayanti; Herry Susanto (South East Asia Nursing Research, 2022)
Inadequate pain management has been a worldwide concern for hospitalized children. Little is known about pain management for pediatric patients in Indonesia. This study explored nurses' experiences providing pain management in the pediatric unit.  A qualitative descriptive approach was used. Fifteen nurses who worked in the pediatric intensive care unit and the pediatric, maternal-child, and general wards of the Islamic Teaching Hospital in Indonesia were interviewed by telephone due to the COVID-19 pandemic period. Based on content analysis, five themes were extracted from the data: ways to assess pain vary, working with colleagues, attitudes toward pain-relief strategies, enhancing parental understanding and involvement, and desire to have age-specific pain management training for pediatric patients. The results revealed issues nurses face in real contexts. Pediatric nurses need pain management training to improve their knowledge and skills.